Iterative methods for solving general Trifunction Variational Inequalities - Netra Kumar Gupta; Suja Varghese; M. A. Siddiqui (International Journal of Mathematics And its Applications, 2023)
In this paper, we describe and discuss the new concept of trifunctional variational inequality. We propose and examine implicit iterative approaches for solving trifunction variational inequalities using the auxiliary principle methodology and nonlinear operator. The convergence conditions of this novel approach are investigated under the pseudomonotonicity requirement, which is a weaker criterion than monotonicity. Some special cases are also taken into account as well.